Contribution to investigations of sternal muscle (m. sternalis) - Malinowski, Andrzej; Otulakowski , Bolesław (Anthropological Review, 1974)
The authors have investigated the above mentioned muscle in 18 anencephalic fetuses, 110 corpses of adults and 350 living young students. They have found this muscle present in 44.4% fetuses, 3.6% corpses and 3.1% living individuals. In discu- ssion authors compare their material with results obtained by other investigators.